Karakterisasi Geokimia Dan Identifikasi Hemiselulosa Pada Kayu Petrisian Danfosil Insitu Araucarioxylondi Kawasan Geopark Merangin - Sutrisno; James Perdinan; Sukmal Fahri (Universitas Jambi, 2018)
The purpose of this study was to determine the chemical elements, the types of mineral compounds, isolate and identify the possibility of the existence of hemicellulolsa content as one of the main constituents of wood structure, and to describe the possibility of fossilization process that has happened to fossil insitu Araucaryoxillon and petrisian wood which is encountered in the Merangin Geopark area. This research was conducted in Merangin Geopark Area in Merangin District of Jambi Province. This research was conducted in 2015. From the research result, it can be concluded that the most elemental content in fossil insitu Araucaryoxillon contained in Merangin Geopark is Silicon (Si) and most of the minerals that make up the fossil are Silica (SiO2). Other elements found are carbon (C), oxygen (O) and Nitrogen (N) in each observed fossil, the presence of hemicellulosa isolated by extraction techniques using NaOH is no longer detectable in Araucaryoxillon insitu fossil or petrisian wood is present in the Merangin Geopark, and in terms of the chemical composition found in this study, silification process of Insitu Araucaryoxillon fossil and petrisian wood formed in the Merangin geopark region is the process of replacement of organic elements by silica minerals.